(untitled) (LEARNing Landscapes, 2019)
As two white female teachers, we look back on our teaching experiences in Hong Kong and Northern Alberta to disrupt problematic diversity narratives from our first classrooms. Through critical auto-ethnographic approaches and cellphilming (cellphone + video-production), we analyze our engagement with privilege within our classrooms. We found that we both promoted uncomplicated conceptions of diversity, and each engaged in what Eve Tuck (2009) has described as damaged-centered approaches—teaching practices that established, “harm or injury in order to achieve reparation” (p. 413). We see these experiences as a case study in how to look back productively to change the way we teach in the present and future toward visions of justice.